An optimized antibody-single-chain TRAIL fusion protein for cancer therapy - Siegemund, Martin (MAbs, 2016)
Fusion proteins combining oligomeric assemblies of a genetically obtained single-chain (sc) variant of tumor necrosis factor-related apoptosis-inducing ligand (TRAIL) with antibodies directed against tumor-associated antigens represent a promising strategy to overcome the limited therapeutic activity of conventional soluble TRAIL. To further improve the scTRAIL module in order to obtain a robust, thermostable molecule of high activity, we performed a comprehensive analysis of the minimal TNF homology domain (THD) and optimized linkers between the 3 TRAIL subunits constituting a scTRAIL. Through a stepwise mutagenesis of the N- and C-terminal region and the joining linker sequences, we generated bioactive scTRAIL molecules comprising a covalent linkage of the C-terminal Val280 and the N-terminal position 122 by only 2 amino acid residues in combination with conservative exchanges at positions 122 and 279. The increased thermal stability and solubility of such optimized scTRAIL molecules translated into increased bioactivity in the diabody-scTRAIL (Db-scTRAIL) format, exemplified here for an epidermal growth factor receptor-specific Db-scTRAIL. Additional modifications within the diabody linkers resulted in a fusion protein exerting high, target-dependent apoptosis induction in tumor cell lines in vitro and potent antitumor activity in vivo. Our results illustrate that protein engineering of scTRAIL and associated peptide linkers provides a promising strategy to develop antibody-scTRAIL fusion proteins as effective antitumor therapeutics.